Attribution - Weary, Gifford. author. aut Link
X, 244 p.
Keywords: This book initially was conceived in 1986 by Weary and Harvey as a revi sion and update of their 1981 Perspectives on Attributional Processes (pub lished by Wm. C. Brown," Dubuque, Iowa). However: toe extensive nature of recent work on attributional processes and the opportunity to collabo rate with Melinda Stanley as a coauthor led to a plan to develop a more comprehensive work than the 1981 book. It definitely is an amalgam of our interests in social and clinical psychology. It represents our commitment to basic theoretical and empirical inquiry blended with the applications of ideas and methods to understanding attribution in more naturalistic set tings, and as it unfolds in the lives of different kinds of people coping with diverse problems of living. The book represents a commitment also to the breadth of approach to attribution questions epitomized by Fritz Heider's uniquely creative mind and work in pioneering the area. To us, the attribu tional approach is not a sacrosanct school of thought on the human condi tion. It is, rather, a body of ideas and findings that we find to be highly useful in our work as social (JH and GW) and clinical (GW and MS) psychology scholars. It is an inviting approach that, as we shall describe in the book, brings together ideas and work from different fields in psychology-all concerned with the pervasive and inestimab1e importance of interpretive activity in human experience and behavior.